VD_FINDINFO HC / 2015 / 1039 vom 11. November 2015 - VD Tribunal cantonal (2015)
AMENDE, COMPARUTION PERSONNELLE, ABSENCE INJUSTIFIÉE, AUTORITÉ DE CONCILIATION | 128 al. 1 CPC (CH), 147 CPC (CH), 204 al. 1 CPC (CH), 204 al. 3 CPC (CH), 206 al. 1 CPC (CH), 206 al. 2 CPC (CH)